Development of immunohistochemical triple staining method for the evaluation of different types of cell death in coronary thrombus - Pertiwi, K R; de Boer, O J; Gabriels, P; Mackaaij, C; van der Wal, A (Journal of physics. Conference series, 2019)
Immunohistochemistry is a powerful technique to identify the presence, distribution and extent of certain antigens at protein level in tissue specimen. Multiple immunostainings enable the detection, colocalization and comparison of several markers within one specimen. However, an optimization study is firstly needed to ensure the expression of multiple markers is clear and distinguishable. We formulated an optimized sequential triple immunostaining protocol which could identify the simultaneous presence of three types of cell death namely necrosis, apoptosis and etosis. These following antibodies were used: C-reactive protein (CRP, necrosis), (cleaved) Caspase-3 (Casp3, apoptosis) and citrullinated-Histone3 (CitH3, etosis). Several antigen retrieval methods, various concentration and order combinations of those antibodies as well as different combination color of chromogens were tested on coronary thrombus materials obtained from patients with acute myocardial infarction (AMI). The results showed that CRP (1:4000) visualized with 3,3'-diaminobenzidine (DAB) in brown, is better performed as the first staining, followed by CitH3 (1:8000) visualized with Perma Blue as the second staining and Casp3 (1:500) visualized with Perma Red as the last staining. In conclusion, we presented an immunohistochemical triple staining protocol to identify the comparative presence of different types of cell deaths: necrosis, apoptosis and etosis in coronary thrombus specimens.